Critical Studies on Integrating Land-Use Induced Effects on Climate Regulation Services into Impact Assessment for Human Well-Being - Zhihui Li; Xiangzheng Deng; Jikun Huang; Rongrong Zhang; Juan Huang (Advances in Meteorology)
It is commonly acknowledged that land use changes (LUC) and climate changes have exerted significant effects on ecosystem services which are essential and vital to human well-being. Among all the services provided by ecosystem, climate regulation services are relatively sensitive to LUC and climate changes. This study aims to comprehensively review studies on the complex effects of LUC and climate changes on climate regulation services and further integrates the effects on climate regulation services into impact assessment for human well-being. In this study, we firstly introduced research efforts in which the drivers of and their corresponding effects on climate regulation services are briefly identified. Then, we explicitly reviewed the researches on the effects of LUC and climate changes on climate regulation services, especially focused on the certain methods and models used to quantify the effects on the major drivers of climate regulation services. After that, the effects of LUC and climate changes on human well-being via climate regulation services were revisited and commented accordingly. Finally, this paper discussed the current research gaps and proposed some research prospects in future studies.